The dramatic text workbook and video : practical tools for actors and directors - Carey, David, 1952-; Carey, Rebecca Clark (Methuen drama, 2019)
"Drama begins with the word. Characters, plot, conflict, genre - all are created through language. An ability to understand how language works is invaluable: actors need to learn not only how to use their voice, but how to use voice and language together. The Dramatic Text Workbook is a textbook which explores the expressive potential of language, and how you as an actor can develop your verbal skills to release that potential. Written by acclaimed voice teachers David Carey and Rebecca Clark Carey (Oregon Shakespeare Festival, RADA) this book provides practical approaches to each aspect of verbal expression with the aid of classical and modern scenes and speeches. Chapters include: · Sound: speech sounds and how to use them more expressively · Image: bring life and specificity to images when you speak · Sense: focus on the most significant words and phrases in a speech or scene · Rhythm: how rhythm is created and used in both verse and prose · Argument: the structure or logic of language A follow-up to The Dramatic Text Workbook, and now including a revised introduction, updated reading lists and a comprehensive revision of the major exercises within the book, it is supported by over 90 minutes of online video workshops, exploring the key techniques and tactics explored in the book"--